2016
DOI: 10.1016/j.athoracsur.2016.02.078
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Versus Open Esophagectomy for Esophageal Cancer: A Population-Based Analysis

Abstract: Background The objective of this study was to evaluate outcomes of minimally invasive approaches to esophagectomy using population-level data. Methods Multivariable regression modeling was used to determine predictors associated with the use of minimally invasive approaches for patients in the National Cancer Data Base who underwent resection of middle and distal clinical T13N03M0 esophageal cancers from 2010 to 2012. Perioperative outcomes and 3-year survival were compared between propensity-matched groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 20 publications
7
90
0
2
Order By: Relevance
“…83,84 There are no major differences in survival between any of the established approaches. 31,80,82,85,86 Standardisation of the surgical approach might be a more important prognostic factor than selecting one specific procedure over another. 87 Alternatively, providing the surgeon has sufficient experience of various surgical approaches, the approach can be tailored depending on tumour and patient characteristics.…”
Section: Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…83,84 There are no major differences in survival between any of the established approaches. 31,80,82,85,86 Standardisation of the surgical approach might be a more important prognostic factor than selecting one specific procedure over another. 87 Alternatively, providing the surgeon has sufficient experience of various surgical approaches, the approach can be tailored depending on tumour and patient characteristics.…”
Section: Surgical Approachmentioning
confidence: 99%
“…31,80 Earlier studies examining minimally invasive surgery showed a high risk of complications, possibly related to learning curve issues, while recent data show accelerated recovery, which has prompted its increased use. 81,82 On-going RCTs are comparing postoperative outcomes following minimally invasive procedures and open surgery, where HRQOL is a key outcome (ISRCTN59036820, NCT01544790, NTRTC2452). Transhiatal and minimally invasive surgery seem to be associated with fewer pulmonary complications compared to thoraco-abdominal approaches.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Also postoperative morbidity rates, the length of stay in intensive care unit and the length of hospital stay did not significantly differ. Also Yerokun et al (21) recently failed to find any clear advantage of the robotassisted esophagectomy using population-level data. They compared perioperative outcomes and 3-year oncologic results obtained after open (n=2,958), standard minimally invasive esophagectomy without robotic assistance (n=1,077) and robot-assisted esophagectomy (n=231) for cT1-3N0-3M0 cancer of the middle or distal esophagus.…”
Section: Robotic Esophagectomy For Cancermentioning
confidence: 99%
“…Esophagectomy is technically challenging and is associated with high morbidity and mortality rates. Efforts to reduce these rates have spurred the adoption of minimally invasive techniques (2). The limitations of this approach, such as the two-dimensional (2D) view or movement restrictions, can, however, make a complex procedure such as esophagectomy difficult.…”
Section: Introductionmentioning
confidence: 99%